(الآيات القرآنية في علم البيان ودورها في تنمية القيم الأخلاقية (كتاب البلاغة الواضحة - Sofiyatullailiyah; Ach Tabrani (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2018)
There is no doubt that the Qur'anic verses have rhetorical methods that are not intended for themselves but for the ends and goals that are hidden in their beautiful secrets. One of these methods is the such as the Tashbih, Majaz, and Kinayah. This study was aimed at revealing the secrets of from the Qur'anic verses contained in the Book of Balaghah Al Wadihah and its role in the development of the moral values for the first semester students of the language preparatory departement. The approach taken by the researcher collect the study material was the method of analytical description by gathering the Qur'anic verses contained from ilmu bayan describing the phenomena, event or thing and collecting the information data and observations about the topic as well as describing the circumtances, where it depends on the collected information of the role of Qur'anic verses in developing ethical values. This study showed that the Qur'anic verses in ilmu bayan included fourteen ethical values and played an instrumental role in the development of these ethics for the students at STIBA Ar-Raayah.